2014
DOI: 10.1017/jfm.2014.570
|View full text |Cite
|
Sign up to set email alerts
|

Flow past a transversely rotating sphere at Reynolds numbers above the laminar regime

Abstract: The flow past a transversely rotating sphere at Reynolds numbers of $\mathit{Re}=500{-}1000$ is directly simulated using an unstructured finite volume collocated code. The effect of rotation rate on the flow is studied by increasing the dimensionless rotation rate, ${\it\Omega}^{\ast }$, from 0 to 1.20, where ${\it\Omega}^{\ast }$ is the maximum sphere surface velocity normalised by the free stream velocity. This study investigates the marked unsteadiness of the flow structures at $\mathit{Re}=500{-}1000$. Com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 45 publications
3
21
0
Order By: Relevance
“…case (e) and case ( f ), the recirculation bubble is evidently mostly suppressed. This near wake is very similar to the 'shear-layer instability' regime reported by Giacobello et al (2009), Kim (2009) and Poon et al (2014) for rigidly mounted rotating spheres at low Reynolds number (Re 1000). They reported single-sided shedding on the advancing side of the rotating sphere.…”
Section: Modes Of Vortex Formationsupporting
confidence: 85%
See 3 more Smart Citations
“…case (e) and case ( f ), the recirculation bubble is evidently mostly suppressed. This near wake is very similar to the 'shear-layer instability' regime reported by Giacobello et al (2009), Kim (2009) and Poon et al (2014) for rigidly mounted rotating spheres at low Reynolds number (Re 1000). They reported single-sided shedding on the advancing side of the rotating sphere.…”
Section: Modes Of Vortex Formationsupporting
confidence: 85%
“…Previous studies (e.g. Giacobello, Ooi & Balachandar 2009;Kim 2009;Poon et al 2014, and references therein) have shown that the onset of the shear-layer instability wake state of a non-oscillating rotating sphere occurs beyond this α value. That wake state forms when fluid that passes the retreating side of the sphere is pushed towards the other side of the wake to form a distinctive one-sided separating shear layer, thus changing the characteristic formation and release of vortex loops that defines the non-rotating wake state.…”
Section: Effect Of Rotation On the Vibration Responsementioning
confidence: 87%
See 2 more Smart Citations
“…Previous numerical studies on the effect of rotation on rigidly mounted rotating spheres at low Reynolds numbers (Re ≤ 300) ( [7], [4]) revealed suppression of the vortex shedding for a certain range of spin ratios. So can the structural vibrations of a sphere be suppressed by an imposed rotation once the sphere is free to oscillate?…”
Section: Introductionmentioning
confidence: 93%